Determination of rational conditions for the movement of transport and technological units when using technological machines with driving wheels - Shuliak, Mykhailo; Chepizhnyi, Andrii; Khvorost, Tetiana; Sokolik, Serhii; Murchych, Maksym (Technology audit and production reserves, 2025)
The object of research is the operation process of a transport and technological unit with the driving wheels of a technological machine. One of the most problematic areas of the effective operation of an energy-intensive tractor as part of a transport and technological unit is the incomplete use of the potential capabilities of the tractor engine. This is due to the fact that at the beginning and at the end of the technological operation the mass of the load of the technological machine will be different. A possible solution to this problem is the use of additional driving axles of the technological machine, which allows to increase the relative share of the coupling weight in the unit. This allows part of the engine power to be realized through the tractor's running system, and part to be transferred to the technological machine. During the study, it was found that when transferring part of the power to the technological machine, three modes of movement are possible: РkT > Pxm; РkT = Pxm; РkT < Pxm. For their analysis, taking into account the dynamic components of the movement, an equivalent dynamic model of the transport and technological unit was used. The oscillations of longitudinal forces acting on the unit characteristic of each mode of movement were obtained. It was found that the movement of the unit with the transmission of part of the power to the drive wheels of the technological machine must be implemented under the movement condition РkT > Pxm, i. e. under partial underload. This is due to the fact that the proposed movement mode allows stabilizing the oscillations of longitudinal forces and increasing the part of the engine power that can be realized in the traction mode. In particular, for this movement condition, the potential traction force Рka increases to 45.92 kN with a decrease in the mean square deviation σka = 1.74 kN. Also, this movement mode is characterized by the absence of the technological machine running into the tractor, as a result, there are the smallest dynamic oscillations and a stabilizing effect for longitudinal forces. Due to this, the possibility of activating the wheels of the technological machine with compensation for the negative factors inherent in the movement of all-wheel drive vehicles is ensured. Compared with similar known methods of using full engine power for transport and technological units with variable mass, ensuring a certain movement condition will increase the efficiency of their work.